EFEKTIFITAS AROMATERAPI PEPPERMINT DAN AKUPRESUR PERIKARDIUM ENAM TERHADAP PENURUNAN EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I DI UPT PUSKESMAS GANTUNG KABUPATEN BELITUNG TIMUR TAHUN 2025 - Ristawani Simamora Purba, Rina; Hidayani, Hidayani; Hanifa, Fanni (PT.Mantaya Idea Batara, 2025)
Background:Emesis gravidarum, commonly characterized by nausea and occasional vomiting, affects many women during the first trimester of pregnancy. Although generally self-limiting, it can significantly reduce quality of life and daily functioning. Objective:This study aimed to assess the effectiveness of peppermint aromatherapy and Pericardium 6 (P6) acupressure in alleviating symptoms of emesis gravidarum in first-trimester pregnant women. Methods:A qualitative case study approach was employed. Two pregnant women in their first trimester experiencing emesis gravidarum were selected using purposive sampling. Data were collected through in-depth interviews and direct observation. The severity of nausea and vomiting was measured using the Pregnancy-Unique Quantification of Emesis (PUQE) score before and after the interventions. Results:Peppermint aromatherapy reduced PUQE scores from 9 (moderate) to 6 (mild), while Pericardium 6 acupressure reduced PUQE scores from 10 (moderate) to 3 (mild). This indicates that both interventions were effective in reducing nausea and vomiting, with Pericardium 6 acupressure showing greater effectiveness. Conclusion:Both peppermint aromatherapy and Pericardium 6 acupressure are effective non-pharmacological methods for reducing emesis gravidarum in the first trimester. Pericardium 6 acupressure demonstrated greater effectiveness and may be recommended as a complementary therapy for managing early pregnancy-related nausea and vomiting